Money, Distribution Conflict and Capital Accumulation 2008
DOI: 10.1057/9780230595606_17
|View full text |Cite
|
Sign up to set email alerts
|

On the (In-)stability and the Endogeneity of the Normal Rate of Capacity Utilization in a Post-Keynesian/Kaleckian ‘Monetary’ Distribution and Growth Model

Abstract: http://www.imk-boeckler.de On the (in-)stability and the endogeneity of the 'normal' rate of capacity utilisation in a post-Keynesian/Kaleckian 'monetary' distribution and growth model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…8 See also Hein (2014b, Chapter 11) and Lavoie (2014, Chapter 6.5) for summaries of the debates. inflation targeting monetary policies when the interest cost and distribution channels of interest rate policies are considered (Hein 2006a.…”
Section: Endogenous Rate Of Capacity Utilisation Beyond the Short Run?mentioning
confidence: 99%
“…8 See also Hein (2014b, Chapter 11) and Lavoie (2014, Chapter 6.5) for summaries of the debates. inflation targeting monetary policies when the interest cost and distribution channels of interest rate policies are considered (Hein 2006a.…”
Section: Endogenous Rate Of Capacity Utilisation Beyond the Short Run?mentioning
confidence: 99%
“…Firms' assessment of trend growth and the normal rate of utilization may endogenously adjust to actual experience (Lavoie 1995a(Lavoie , 1996. And finally, the target or normal rate as a stable inflation rate of utilization may itself be endogenous to inflation targeting monetary policies when the interest cost and distribution channels of interest rate policies are considered (Hein 2006;2008, chapter 17).…”
Section: A Steindlian Model Of Distribution Growth and Stagnationmentioning
confidence: 99%
“…Theoretically, they are very close to the idea embedded in the standard NAIRU models: There is a long-run equilibrium, determined by structural characteristics of the labour market, which is independent of the short-run fluctuations generated by demand shocks or macroeconomic policy. We do not share this view (Hein 2004(Hein , 2006a(Hein , 2006b period, therefore, it must be concluded that fiscal policy in the USA has played its macroeconomic stabilisation role properly, whereas in the Euro area fiscal policy has acted in an often pro-cylical and therefore destabilising way For the individual Euro area countries the picture is rather diverse (Table 5) …”
Section: The Macroeconomic Impact Of Fiscal Policymentioning
confidence: 85%
“…5 The ECB has tended to tighten whenever inflation increased above the target without relaxing when inflation expectations came down. For a general critique of the ECB's 'anti-growth bias' see Bibow (2002Bibow ( , 2005aBibow ( , 2005b Hein (2002) and Hein/Truger (2006b Hein (2006aHein ( , 2006b) for the integration of real debt effects into Kaleckian models of distribution and growth with conflict inflation.…”
Section: The Macroeconomic Impact Of Monetary Policy and Wage Developmentioning
confidence: 99%